Perbandingan Sistem Administrasi Negara Indonesia Dengan Sistem Administrasi Negara Thailand - Afifah Dina Fatin (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2023)
In the study of Comparative Public Administration, there is a relevant aspect, namely the aspect of Public Administration which contains a general understanding of how state institutions grow and live in a country carrying out their functions. State administration is not a field of study that has a general understanding and nature and stands alone, but is a field of study that is not applied in a country with multidisciplinary. State administration is essentially one aspect of administration that emphasizes discussion in the field of statehood. Various opinions have suggested the definition or limits of administration which is the parent of state administration, but in general it can be identified that the definition or limits contain elements: elements of the organizing process, elements of cooperation carried out by more than one person and. elements of achieving predetermined goals. The structure of government can be interpreted as a complete request consisting of various parts of government that work together relying on and influencing in achieving the objectives and elements of government. Despite the fact that each country's system of government may differ from one another. Our insights can also be used as a comparison for our country because we will gain an understanding of other countries' government systems. Therefore, once we know the similarities and differences between the various systems of government, we can design a system that is considered superior.